Kontrol diri dan kepribadian ekstrovert dengan impulsive buying pada individu yang melakukan belanja online - Finanin Nur Indana; Elfa Khorifa Izlia Aqnuri (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2022)
This study aims to to know whether there is a self control and relations with impulsive buying extroverted personality.A subject in this research expenditure those who do online.Using a technique purposive sample taken with the sampling method of and wear the theory table of isaac & amp; michael in determining the number of respondents sample and obtained 272.The analysis used namely linear regression and the worship of idols and from the results of the analysis indicates that the existence of a significant relation exists between self control and extroverted personality with impulsive to be buying to the expenditure.In addition self control and extroverted personality makes a contribution effective as much as 13.5 % of impulsive buying and the rest 86.5 % influenced by a factor of who have not yet researched by researchers.